An Active Fraction of Trillium tschonoskii Promotes the Regeneration of Intestinal Epithelial Cells After Irradiation - Song, Feiling; Wang, Sihan; Pang, Xu; Fan, Zeng; Zhang, Jie; Chen, Xiaojuan; He, Lijuan; Ma, Baiping; Pei, Xuetao; Li, Yanhua (Frontiers in Cell and Developmental Biology, 2021)
Despite significant scientific advances toward the development of safe and effective radiation countermeasures, no drug has been approved for use in the clinic for prophylaxis or therapy of radiation-induced acute gastrointestinal syndrome. Thus, there is an urgent need to develop potential drugs to accelerate the repair of injured intestinal tissue. In this study, we investigated that whether some fractions of traditional Chinese medicine (TCM) have the ability to regulate intestinal crypt cell proliferation and promotes crypt regeneration after radiation. By screening the different supplements from a TCM library, we found that an active fraction of the rhizomes of Trillium tschonoskii, TT-2, strongly increased the colony-forming ability of irradiated IEC-6 cells. TT-2 significantly promoted the proliferation and inhibited the apoptosis of irradiated IEC-6 cells. Furthermore, in a small intestinal organoid radiation model, TT-2 promoted irradiated intestinal organoid growth. More importantly, TT-2 remarkably enhanced the repair of the intestinal epithelium of mice after abdominal irradiation. Mechanistically, TT-2 remarkably activated the expression of intestinal stem cell-associated and proliferation-promoting genes and inhibited apoptosis-related gene expression. Our data indicate that active fraction of TT can be developed into a potential oral drug for improving the regeneration and repair of intestinal epithelia that have sustained radiation damage.